Sglt-2 Inhibitors in Diabetic Type 2 Patients Nephroprotective Effects of (Empagliflozin) (Eurasian Journal of Research, Development and Innovation, 2023)
Study of the effect of SGLT-2ingibitors on kidney function in Diabetes Mellitus Type 2 patients